The key factors influencing talent development in this competitive digital age and recommendations for Robi Axiata Limited. - Arnob, Rafid Hasan (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.